Bath Temperature-Dependent Growth of Nanocrystalline Bi2s3 Films Via a Seed-Layer-Assisted Approach for Photoelectrochemical Applications - Radhalayam, D (Elsevier B.V., 2025)
Bismuth sulfide (Bi2S3) is a promising photoelectrode material for photoelectrochemical (PEC) water splitting, but its efficiency is limited by poor charge transport and rapid carrier recombination. In this work, Bi2S3 films were fabricated via a seed-layer-assisted chemical bath deposition process, and the influence of bath temperature on their structural, optical, and PEC properties was systematically investigated. Morphological evolution from compact grains at 30 °C to vertically aligned nanorods at 50 °C, accompanied by increased porosity at higher temperatures, was observed. Elemental analysis indicated temperature-dependent variations in the Bi/S ratio, reflecting altered growth kinetics. Optical studies revealed slight bandgap shifts, while PEC measurements showed a steady increase in photocurrent density with temperature, reaching 11.6 mA/cm2 at 70 °C due to improved film thickness and porosity. The film deposited at 80 °C exhibited the highest photocurrent stability. Electrochemical impedance spectroscopy further confirmed reduced charge-transfer resistance at elevated temperatures, highlighting enhanced charge separation. These results demonstrate that bath temperature is a key parameter for tuning Bi2S3 film properties and provide a simple, scalable strategy to improve PEC water splitting efficiency. © 2025 Elsevier B.V.